(untitled) (Journal of actual problems of jurisprudence, 2018)
Thise article discuss about criteria and corresponding to them indexes of socio-economic development of regions are considered in the conditions of included of Republic of Kazakhstan in the number of the fifty most developed countries of the world. Socio-economic development is based on four main factors: population, natural resources, formation of capital, technique. Key words: region, developed countries, social development, economy growing, intellectual potential.